Corporate Debt Restructuring in East Asia : Some Lessons from International Experience - Stone, Mark. (Washington, D.C. : International Monetary Fund, 1998)
This paper summarizes some lessons from international experience for corporate debt restructuring in east Asia. Basic principles of debt restructuring are described, the experiences of Mexico, Chile, the United Kingdom, Hungary, and Poland are examined, and general lessons are drawn. The approaches currently being adopted in Indonesia, Korea, Malaysia and Thailand are then reviewed in the context of these lessons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet